Magnetic resonance imaging for three-dimensional printing of the bony orbit: is clinical use imminent?. Issue 4 (April 2020) - Cooper, T.; Schmutz, B.; Hsu, E.; Lynham, A.
Abstract: The aim of this study was to examine the accuracy of three dimensionally (3D) printed models of the bony orbit derived from magnetic resonance imaging (MRI) for the purpose of preoperative plate bending in the setting of orbital blowout fracture. Retrospective computed tomography (CT) and MRI data from patients with suspected orbital fractures were used. Virtual models were manually generated and analysed for spatial accuracy of the fracture margins. 3D-printed models were produced and orbital fan plates bent by a single operator. The plates were then digitized and analysed for spatial discrepancy using reverse engineering software. Seven orbital blowout fractures were evident in six orbits. Analysis of the virtual models revealed high congruence between blowout fracture margins on CT and MRI ( n = 7, average deviation 0.85 mm). Three zygomaticomaxillary complex fractures were seen, for which MRI did not demonstrate the same accuracy. For plates bent to the 3D-printed models of blowout fractures ( n = 6), no significant difference was found between those bent to CT versus those bent to MRI when compared for average surface and average border deviation (Wilcoxon signed rank test). Orbital blowout fractures can be defined on MRI with clinically acceptable accuracy. 3D printing of orbital biomodels from MRI for bending reconstructive plates is an acceptable and accurate technique.